Blockchain technology and application : second CCF China Blockchain Conference, CBCC 2019, Chengdu, China, October 11-13, 2019, Revised selected papers /: second CCF China Blockchain Conference, CBCC 2019, Chengdu, China, October 11-13, 2019, Revised selected papers. (2020) - Unknown
No abstract available